PERANCANGAN KNOWLEDGE MANAGEMENT SYSTEM BERBASIS WIKI UNTUK PENGELOLAAN PENGALAMAN MAHASISWA PRAKTIK - Mahersy Bobode; Frederik Samuel Papilaya; Michael Bezaleel Wenas (CCIT Journal, 2016)
Clinic practicum program of Faculty of Health, of Satya Wacana Christian University, is one of the program with the purpose to carry on students’ clinic learning which is integrated the theory and practical work at hospital. In the practical work, mental readiness of the students is one of the important factors to reduce the level of anxiety in facing with the real problem in practical work at hospital. The problem that is often occurred is that the students hard to adapt with the hospital’s custom. Therefore, in order to solve the problem, the action that has been chosen is to gain experience from the previous practicum students to richen knowledge and in the other hand, to reduce anxiety level and also to support the process of adaptation. This research discussed the way to design Knowledge Management System to process the experience of practicum students, in order to support the process of students’ adaptation, and to increase the tradition of clinic sharing experience among students. This research uses a qualitative manner with interview and observation as the method of collecting data. As the output, this research produce a wiki application that can be used as the media to facilitate students in sharing the knowledge which is expected to support the students adaptation process, also to increase the sharing tradition of clinic practicum among students of Faculty of Health of Satya Wacana Christian University.